Modified Binary Particle Swarm Optimization for Solving Distribution Network Reconfiguration - Ali Nasser Hussain (Journal of Madenat Alelem University College, 2018)
This study utilized Binary Particle Swarm Optimization (BPSO) and Modified BPSO (MBPSO) for solving Distribution Network Reconfiguration (DNR). The search problem space for the presented algorithm is a set of lines (switches) which are normally closed or opened, this search problem may be dissimilar for different dimensions. This paper consists of two parts. First, the reconfiguration with constant load was optimized based on two algorithms BPS and MBPS. The decreasing of real power loss has been invested as an objective function; while node voltage, system radially and line current have been utilized as limits of the system. Second, the reconfiguration with variable load is optimized based on the same two algorithms BPS and MBPS. The proposed methods are applied on IEEE node  power system by using  software to test the effectiveness and efficiency of MBPSO algorithm. The results for the IEEE node  power systems indicate that algorithm has high ability and effective in reduce power loss and voltage profile enhancing of the system compared to